Penerapan Model Project Based Learning (Pjbl) Untuk Meningkatkan Hasil Belajar Matematika Materi Bangun Datar Pada Siswa Kelas IV SDN Inpres 5/81 Tendeki - Pongayow, Paulina Ester; Rorimpandey, Widdy H.F.; Ester, Kartini (Peneliti.net, 2024)
This research aims to improve mathematics learning outcomes for flat shapes in the combined area of flat shapes (squares, rectangles and triangles) by implementing the Class IV Project Based Learning (PjBL) Model at SDN INPRES 5/81 Tendeki. The research uses the classroom action research (PTK) method proposed by Kemmis and Mc Taggart and consists of two cycles where each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The research results showed that the percentage of learning outcomes obtained by students in cycle I was 66.78% and in cycle II it increased to 82.14%. Based on the results of this research, it was concluded that the Project Based Learning (PjBL) model could improve Mathematics learning outcomes for the Flat Build material in class IV students at SDN INPRES 5/81 Tendeki. Researchers provide suggestions for teachers so that Mathematics learning outcomes are more optimal and can achieve KKM targets, it is recommended to place more emphasis on the use of learning models using the Project Based Learning Model (PjBL).